Rural Microarcologies - a vision of resilient future architecture - Arnby, Anton (My University, 2020)
With the advent of climate change, humanity is facing monumental changes. Overconsumption of resources and fossil fuels are leading us into catastrophic ecological decline, and the end of the growth-centered society we live in is arriving, whether through disaster or design. Agriculture in Sweden is optimised for the smallest possible workforce and is largely dependent on fossil fuel. Repopulating the rural areas can enable the transition to a more sustainable agriculture, as well as making more variable and fulfilling lifestyles possible in a post-growth world, where personal satisfaction is not dependent on consumption of material goods and resources. Using sequential art and storytelling, I propose a new type of dwelling that can improve the local agricultural communities and help create more sustainable lifestyles. This typology, dubbed Microarcology, is a dense dwelling operating at a high level of self-sufficiency, and works in concert with the surrounding community and landscape to create sustainable energy cycles while fostering social relationships on the local and regional scale. The resulting design proposal is a vision of ruralisation that can provide inspiration for further discussions about the design of a sustainable future.
Keywords: resilience, ruralisation, co-housing, shared spaces, cradle to cradle